Fractional PI Stabilization of Delay Systems: Application to a Thermal System - Rhouma, Aymen; Hafsi, Sami; Laabidi, Kaouther (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, an application of fractional-order PIλ controller is given as an alternative to solve some control problems that can arise. It aims to apply the analytical tuning procedure to control the heat ﬂow systems. This system, modeled by ﬁrst-order system involving time delay, is one with open loop characteristic equations are fractional order quasi-polynomials. Using the proposed method, the entire stability region of PI λ controllers is obtained and visualized in the plane (Kp,Ki, λ ). The simulation was carried out on thermal systems and the results demonstrate the eﬀectiveness of the proposed type of controllers and the tuning rule.